Trauma-tragedy : symptoms of contemporary performance - Duggan, Patrick, 1981- (Manchester University Press, 2012)
Trauma-Tragedy investigates the extent to which performance can represent the 'unrepresentable' of trauma. Throughout, there is a focus on how such representations might be achieved and if they could help us to understand trauma on personal and social levels. In a world increasingly preoccupied with and exposed to traumas, this volume considers what performance offers as a means of commentary that other cultural products do not.